Mexico in crisis, the U.S. to the rescue : the financial assistance packages of 1982 and 1995 - Lustig, Nora (Brookings Institution WashingtonUS, 1996)
Focuses on the role played by the United States in providing financial assistance packages in 1982 and 1995 to Mexico. Compares both rescue packages and seeks to explain what led to some of the main differences in the U.S. response.